2019
DOI: 10.1088/1361-648x/ab47a5
|View full text |Cite
|
Sign up to set email alerts
|

Band offsets engineering in asymmetric Janus bilayer transition-metal dichalcogenides

Abstract: Using the first-principles calculation, we systematically studied the electronic properties of the bilayer transition metal dichalcogenides (TMDs) MX 2 (M = Mo, W; X = S, Se, Te) with replacing one, two, three or four layers of X atoms as Y atoms (X ≠ Y = S, Se, Te). By comparison, it is found that when the inner two layers of chalcogenide atoms are different, the system has both valence band offset (VBO) and conduction band offset (CBO). Among them, values of the band offsets reach maxima when the inner one l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…This out-of-plane coefficient was also found to increase via stacking of multilayers with d 33 reaching 10 pm/V for MoSeTe. Using the firstprinciples calculations, Liu et al studied the bilayer transition metal dichalcogenides (TMDs) MX 2 (M = Mo, W; X = S, Se, Te) by replacing one, two, three, or four layers of X atoms as Y atoms and investigated the effect of biaxial strain on the conduction and valence band offsets in these bilayers for their applications in optoelectronic, nanoelectronic, and valleytronic devices, although the 1T phase of Group IVB TMDCs is centrosymmetric, and hence nonpiezoelectric. However, their Janus structures have been computationally shown to have a higher in-plane piezoelectric coefficient than the Mo/W-based monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…This out-of-plane coefficient was also found to increase via stacking of multilayers with d 33 reaching 10 pm/V for MoSeTe. Using the firstprinciples calculations, Liu et al studied the bilayer transition metal dichalcogenides (TMDs) MX 2 (M = Mo, W; X = S, Se, Te) by replacing one, two, three, or four layers of X atoms as Y atoms and investigated the effect of biaxial strain on the conduction and valence band offsets in these bilayers for their applications in optoelectronic, nanoelectronic, and valleytronic devices, although the 1T phase of Group IVB TMDCs is centrosymmetric, and hence nonpiezoelectric. However, their Janus structures have been computationally shown to have a higher in-plane piezoelectric coefficient than the Mo/W-based monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…To assist this fact, the band offset values are evaluated from the position of the band edge in the band structure of WSSe AAA, WSSe, and WSeTe AA′A are listed in Table 2 , which indicates significant values of the band offset (∼0.5 eV). These large values of band offsets suggest the presence of the nondeteriorating parallel dipole moment for stacking layers and can act as a driving force for separating photogenerated carriers, 22 thus confining electrons in the bottom layer and holes in the top layer, which can increase the solar cell’s conversion efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Similar Janus TMDs (JTMDs), where the metal layer has different atomic species on each side, have been documented to exhibit applicable band gaps and, within the ultraviolet to visible light regions, show strong optical absorption by using a first-principles study. , Because of the presence of strong planar asymmetry in JTMDs, the difference in electronegativity of chalcogens causes the formation of a dipole across the plane, which induces an internal electric field. When stacking multiple JTMD layers, the dipoles of the individual layers are stacked and an abrupt thin pn junction can be obtained across the multilayer system; this way, JTMDs can be integrated effectively for optoelectronic and PV devices. For example, Palsgaard et al have demonstrated that three layers of stacked MoSSe Janus structures having type-II band alignment can result in abrupt inherently atomically thin p–n junctions across the layers, and using such a multilayer stacked device, the photocurrent response is higher than that of an analogous thin-film silicon device, explaining the great prospective of stacked Janus in PV technology. Several pieces of studies have been carried out till now to investigate the electrical, mechanical, transport, and optical properties of ML and bilayer Janus MXY (M = W/Mo; X ≠ Y = S, Se, and Te), where all the structures show planar asymmetry resulting in strong dipoles across the plan, indicating their appropriateness in PV applications.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Advanced synthesis techniques allowed obtainment of Janus TMDs, 16 in which one of the chalcogen planes is stripped and replaced with different chalcogen species (i.e., MXY), which can contribute to the formation of intrinsic dipoles perpendicular to the 2D monolayers. This novel class of materials was rapidly subject to numerous studies, exploring band gap engineering, 17,18 valley polarization, 19,20 magnetic anisotropy, 20,21 piezoelectricity, 22,23 and potential applications, such as solar energy conversion. 23,24 A combination of the 2D spatial confinement of layered TMDs and their reduced dielectric screening allows the formation of tightly bound electron−hole pairs, i.e., excitons, which affects the optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…TMDs have also been prominent in the context of van der Waals (vdW) heterostructures, where different 2D materials are stacked to design new materials. , Advanced synthesis techniques allowed obtainment of Janus TMDs, in which one of the chalcogen planes is stripped and replaced with different chalcogen species (i.e., MXY), which can contribute to the formation of intrinsic dipoles perpendicular to the 2D monolayers. This novel class of materials was rapidly subject to numerous studies, exploring band gap engineering, , valley polarization, , magnetic anisotropy, , piezoelectricity, , and potential applications, such as solar energy conversion. , …”
Section: Introductionmentioning
confidence: 99%